Assessing Adolescents' Communicative Self-Efficacy to Discuss Controversial Issues: Findings From a Randomized Study of the Word Generation Program. (2nd July 2016) - Lin, Alex R.; Lawrence, Joshua F.; Snow, Catherine E.; Taylor, Karen S.
Abstract: Communicative self-efficacy serves as an important link between discussing controversial issues and civic engagement because confidence in one's discourse skills is important to managing conflicting perspectives and developing solutions to community-based problems. Freely available to schools, Word Generation is a cross-content literacy program that supports teachers in the four main content areas—ELA, social studies, science, and math—to embed learning of controversial issues through classroom discussions, subject-specific lessons, and writing. Middle school students ( N = 5, 870) from diverse backgrounds participated in a randomized study of the intervention that was conducted in 12 middle schools located in an urban school district. We analyzed survey data based on students' self-reported ratings on their communicative self-efficacy, as indicated by confidence to participate in discussions of 15 different controversial issues related to politics, society, and science. Paired sample t -tests indicate that treatment students reported higher communicative self-efficacy than control students on a set of topics immediately covered prior to testing, but not on the set of topics covered in the previous year. This study informs curriculum developers, policy makers, and educators to consider the importance of incorporating classroom discussions of controversial issues within a framework of subject-specific instruction.